2016
DOI: 10.1371/journal.pone.0168668
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Malaria Knowledge, Beliefs and Attitudes, and Related Factors in the Bata District, Equatorial Guinea

Abstract: ObjectivesAdequate community knowledge about malaria is crucial in order to improve prevention by reducing exposure to the disease. Malaria is a major cause of morbidity and mortality among children of less than five years of age in Equatorial Guinea. However, information concerning the accuracy of community knowledge is insufficient. This study aimed at assessing the depth of caregivers’ knowledge of malaria, their beliefs and attitudes about this disease, and their socioeconomic determinants in the Bata dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 37 publications
5
16
0
Order By: Relevance
“…Recent Equatorial Guinea statistical information shows that in 2012, net enrolment in primary education was only 61%, and probably this number is lower in rural populations [ 40 ]. Romay-Barja et al [ 41 ] studied individual knowledge about malaria in Bata district (urban and rural areas) and reported that almost 65% of the individuals living in the rural areas were unaware of how malaria is transmitted and the use of bed nets were mentioned more to prevent mosquito nuisance than for malaria prevention and this lack of information about malaria prevention tools and practices was frequent in both villages.…”
Section: Discussionmentioning
confidence: 99%
“…Recent Equatorial Guinea statistical information shows that in 2012, net enrolment in primary education was only 61%, and probably this number is lower in rural populations [ 40 ]. Romay-Barja et al [ 41 ] studied individual knowledge about malaria in Bata district (urban and rural areas) and reported that almost 65% of the individuals living in the rural areas were unaware of how malaria is transmitted and the use of bed nets were mentioned more to prevent mosquito nuisance than for malaria prevention and this lack of information about malaria prevention tools and practices was frequent in both villages.…”
Section: Discussionmentioning
confidence: 99%
“…Studies [49,50] measured specific knowledge items unlike the current study that comprehensively measured knowledge. One study in Equatorial Guinea reported closer value, 35%, of combined knowledge score on malaria among rural sub-groups, which is comparable in terms of study population and measurement [52]. The magnitude of ITN utilization is another variable needing explanation.…”
Section: Discussionmentioning
confidence: 96%
“…About 156 pharmacies and other drug sellers are located throughout the rural and urban areas of the District. In rural areas, where the majority of the population lives > 3 km from a health facility, CHWs were trained to manage the malaria diagnosis and treatment [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…A malaria knowledge score was created to categorize respondents with poor or good knowledge, including the caregiver’s knowledge about malarial transmission, disease symptoms, prevention, treatment for children, and treatment centres. Good or poor knowledge of malaria disease symptoms, transmission, and prevention was defined as scores above or within and below the overall median, respectively [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation